OPTIMIZATION OF REFEREE ASSIGNMENT FOR INDONESIAN LIGA 1 - FIRMANSYAH SYAIFUL (NIM: 10114062), ALIEF
A referee is the main football match official who has full in charge to take every decision. The referee is responsible to lead the Fair Play and to conduct the Law of the Game. Referee also has rights to have fairness on a football competition’s assignment portion. The fairness here means that each referee’s assignment is distributed evenly among them. In this final project, the referee assignment for Indonesian major football league named Liga 1 is studied by formulating the referee assignment regulation as the integer linier programming. The optimization problem will be solved using Matlab’s toolbox named intlinprog.